POTENSI TANDAN KOSONG KELAPA SAWIT DAN ECENG GONDOK (Eichhornia crassipes) SEBAGAI BAHAN BAKU PUPUK ORGANIK (Potential of Oil Palm Empty Fruit Bunches and Water Hyacinth (Eichhornia crassipes) As Raw Materials Organic Fertilizer) - Prabawa, I Dewa Gede Putra (Kementerian Perindustrian, 2016)
Oil palm empty fruit bunches and water hyacinth have not been widely used, especially in South Kalimantan. These materials were known containing macro elements that are needed by plants. This research was conducted to study potential of oil palm empty fruit bunches and water hyacinth as raw material for organic fertilizer. The effect of ashing temperature variations (500°C; 750°C; 1000°C) on the macro nutrients content (N, P2O5, and K2O) have been studied. The result showed that the characterization of empty fruit bunches and water hyacinth have the highest P2O5 and K2O content, whereas the content of nitrogen was still lowest. The treatment of ashing temperature was effect on improve total content of N, P2O5 and K2O. The highest nitrogen contents in empty fruit bunches and water hyacinth obtained on ashing temperature 500oC. The highest P2O5 contents in empty fruit bunches obtained on ashing temperature 1000oC and water hyacinth obtained on ashing temperature 750oC. The highest K2O contents in empty fruit bunches obtained on ashing temperature 750oC and water hyacinth obtained on ashing temperature 500oC. Ash of oil palm empty fruit bunches and water hyacinth was potentially as a source of nutrients P2O5 and K2O for organic fertilizer, but less potential as a source of nitrogen.Keywords: oil palm empty fruit bunches, water hyacinth, raw material, organic fertilizer